Fused deposition modeling based polymeric materials and their performance: A review - Shanmugam, Vigneshwaran; Pavan, Munagoti Venkata; Babu, Karthik; Karnan, Balamurugan (Polymer composites, 2021)
Additive manufacturing (AM) has several advantages that will make a revolution in polymeric material development. In the AM of polymeric materials, filament deposition modeling (FDM) has been widely used owing to its versatility, low cost, and efficacy. FDM includes different parameters and also an interlayer adhesion that contributes to the performance of the printed parts. In recent years, reinforcement has been introduced in FDM‐printed polymeric materials to improve performance. This review looked at different polymer materials that were printed using the FDM process. A systematic literature search was conducted on FDM‐printed polymers, and the mechanical and thermal performance of these materials was reviewed and critically reported. The performance of FDM printed polymeric materials has been discussed in relation to FDM process parameters, matrix type, fiber reinforcement type, particle reinforcement type, and lattice structure. In a nutshell, this review article will assist researchers working in the field of 3D printing of polymeric materials in understanding the various polymer and polymeric composites' properties and performance.